Cardiovascular disease prevalence and relevance in haemophilia: a scoping review. (24th November 2014) - Rizwan, I.; Minuk, L.; Jackson, S.; Iorio, A.
Summary The prevalence of cardiovascular disease (CVD) risk and events in patients with haemophilia (PWH) is expected to increase as the longevity of this cohort increases due to treatment advances since the 1950s. The aims of this study were to assess publications of CVD and haemophilia for robustness, determine if the increasing longevity of PWH and associated age‐related CVD risk factors result in CVD events; assess the need for an extension of the circle of care for ageing PWH due to the shift in comorbidities. A scoping review was conducted, resulting in a final pool of 30 articles which were organized based on publication dates. A matrix was created to illustrate which articles cited articles published prior to its own publication. This led to the identification of the primary articles, receiving the highest number of citations by other publications, which drive the research pertaining to the study of age‐related risk factors of CVD in PWH. The scoping review revealed 14 original articles, four of which indicated a protective effect of haemophilia toward CVD. Twelve articles demonstrated a similar prevalence of CVD in PWH compared to the general population while seven articles concluded a difference in the prevalence of CVD in the ageing haemophilia population. The existing literature presented conflicting evidence regarding the possibility of a protective effect of haemophilia against CVD. The scoping review was not able to finalize whether the longevity of PWH and their associated age‐related CVD risk factors result in CVD events because the articles assessed reported conflicting results.